Letter (copy) : Miss Gwendolyn Adams de Puertas - Tewson, Vincent
012b-0003-001 HVT/FC/143. Secretary's 8th January, 1938. Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VIIe. Dear Mr. Schevenels, MISS GWENDOLYN ADAMS DE PUERTAS This is a letter to introduce Miss Gwendolyn Adams de Puertas who has called to see me this morning. You will remember that I wrote to you a few days ago in regard to possible assistance which could be rendered, and I wanted your advice concerning the question as to whether it would be possible to say that we had no objection to the Asistencia Social receiving some of the food. The reason I took this precaution was that I am not quite clear as to the actual arrangements which you have made for distribution of the food and I do not want to cut across any recognised procedure which has been adopted. Probably you would be so good as to have a talk with the lady I am introducing and give such information which you feel it is possible to give if any assistance can be rendered. Yours sincerely, Assistant Secretary. 292/946/12b/3